On the Measurement of Procrastination: Comparing Two Scales in Six European Countries - Svartdal, Frode; Pfuhl, Gerit; Nordby, Kent; Foschi, Gioel; Klingsieck, Katrin B.; Rozental, Alexander; Carlbring, Per; Lindblom-Ylänne, Sari; Rębkowska, Kaja (Frontiers in Psychology, 2016)
Procrastination is a common problem, but defining and measuring it has been subject to some debate. This paper summarizes results from students and employees (N = 2893) in Finland, Germany, Italy, Norway, Poland and Sweden using the Pure Procrastination Scale (PPS) and the Irrational Procrastination Scale (IPS) (Steel, 2010), both assumed to measure unidimensional and closely related constructs. Confirmatory factor analyses (CFA) indicated inadequate configural fit for the suggested one-factor model for PPS; however, acceptable fit was observed for a three-factor model corresponding to the three different scales the PPS is based on. Testing measurement invariance over countries and students-employees revealed configural but not strong or strict invariance, indicating that both instruments are somewhat sensitive to cultural differences. We conclude that the PPS and IPS are valid measures of procrastination, and that the PPS may be particularly useful in assessing cultural differences in unnecessary delay.